Ionic Mechanisms of Impulse Propagation Failure in the FHF2-Deficient Heart. Issue 12 (4th December 2020) - Park, David S.; Shekhar, Akshay; Santucci, John; Redel-Traub, Gabriel; Solinas, Sergio; Mintz, Shana; Lin, Xianming; Chang, Ernest Whanwook; Narke, Deven; Xia, Yuhe; Goldfarb, Mitchell; Fishman, Glenn I.
Abstract : Rationale: FHFs (fibroblast growth factor homologous factors) are key regulators of sodium channel (NaV ) inactivation. Mutations in these critical proteins have been implicated in human diseases including Brugada syndrome, idiopathic ventricular arrhythmias, and epileptic encephalopathy. The underlying ionic mechanisms by which reduced Nav availability in Fhf2 knockout ( Fhf2 KO ) mice predisposes to abnormal excitability at the tissue level are not well defined. Objective: Using animal models and theoretical multicellular linear strands, we examined how FHF2 orchestrates the interdependency of sodium, calcium, and gap junctional conductances to safeguard cardiac conduction. Methods and Results: Fhf2 KO mice were challenged by reducing calcium conductance (gCaV ) using verapamil or by reducing gap junctional conductance (Gj) using carbenoxolone or by backcrossing into a cardiomyocyte-specific Cx43 (connexin 43) heterozygous background. All conditions produced conduction block in Fhf2 KO mice, with Fhf2 wild-type ( Fhf2 WT ) mice showing normal impulse propagation. To explore the ionic mechanisms of block in Fhf2 KO hearts, multicellular linear strand models incorporating FHF2-deficient Nav inactivation properties were constructed and faithfully recapitulated conduction abnormalities seen in mutant hearts. The mechanisms of conduction block in mutant strands with reduced gCaV or diminished Gj are very different. Enhanced Nav inactivation due to FHF2 deficiency shifts dependence onto calcium current (ICa ) to sustain electrotonic driving force, axial current flow, and action potential (AP) generation from cell-to-cell. In the setting of diminished Gj, slower charging time from upstream cells conspires with accelerated Nav inactivation in mutant strands to prevent sufficient downstream cell charging for AP propagation. Conclusions: FHF2-dependent effects on Nav inactivation ensure adequate sodium current (INa ) reserve to safeguard against numerous threats to reliable cardiac impulse propagation. Abstract : Supplemental Digital Content is available in the text.